2015
DOI: 10.1586/17476348.2015.1081063
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with respiratory infections in primary care: procalcitonin, C-reactive protein or both?

Abstract: Use of inflammatory biomarkers to guide antibiotic decisions has shown promising results in the risk-adapted management of respiratory tract infections, mainly in the inpatient setting. Several observational and interventional trials have investigated the benefits of procalcitonin (PCT) and C-reactive protein (CRP) testing in primary care. Both markers have shown promising results, although CRP is an inflammatory biomarker while PCT is more specific for bacterial infections. For CRP, point-of-care testing is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…The diagnostic patterns between CRP and HNL were essentially identical whether all patients with respiratory infections were included or only patients with upper respiratory infections were examined. We also confirmed that PCT did not add much to the diagnostic distinction between bacterial and viral causes of acute respiratory infections (1012), although numerous publications have advocated PCT as a tool to manage the antibiotic treatment of such patients (1315). It is possible that the severity of our patients' infections is less than in many of those studies, although our previous results on sepsis also showed the diagnostic superiority of HNL over PCT (16).…”
Section: Discussionsupporting
confidence: 68%
“…The diagnostic patterns between CRP and HNL were essentially identical whether all patients with respiratory infections were included or only patients with upper respiratory infections were examined. We also confirmed that PCT did not add much to the diagnostic distinction between bacterial and viral causes of acute respiratory infections (1012), although numerous publications have advocated PCT as a tool to manage the antibiotic treatment of such patients (1315). It is possible that the severity of our patients' infections is less than in many of those studies, although our previous results on sepsis also showed the diagnostic superiority of HNL over PCT (16).…”
Section: Discussionsupporting
confidence: 68%
“…We have also not discussed in detail other markers of infection such as CRP. However, there is a lack of well-done and large studies comparing the effect of both markers when used in the context of antibiotic stewardship [82, 83]. …”
Section: Introductionmentioning
confidence: 99%
“…Incubation of cells with S. aureus resulted in TNF-α production by mononuclear and granulocytic cells [19,20]. Increased levels of sPCT are, however, attenuated by the release of IFN-γ in response to viral infections, and non-infectious inflammatory stimuli, such as autoimmune disease and chronic inflammatory processes, are much less pronounced, rarely exceeding 0·5 ng/ml [21,22]. These findings demonstrate that TNF-α is the main mediator in the S. aureus-induced stimulation of PCT production in monocytes and granulocytes, as the effect could be almost totally abrogated when the cytokine was neutralized by anti-TNF-α [19].…”
mentioning
confidence: 99%
“…These findings demonstrate that TNF-α is the main mediator in the S. aureus-induced stimulation of PCT production in monocytes and granulocytes, as the effect could be almost totally abrogated when the cytokine was neutralized by anti-TNF-α [19]. Increased levels of sPCT are, however, attenuated by the release of IFN-γ in response to viral infections, and non-infectious inflammatory stimuli, such as autoimmune disease and chronic inflammatory processes, are much less pronounced, rarely exceeding 0·5 ng/ml [21,22]. Interestingly, during these processes, the mature CT peptide concentration either does not increase or is only slightly augmented [16,23].…”
mentioning
confidence: 99%